Effect of Curcumin on Aspergillus Parasiticus Growth and Expression of Major Genes Involved in the Early and Late Stages of Aflatoxin Biosynthesis - A Allameh; M Shams-Ghahfarokhi; Z Jahanshiri; M Razzaghi-Abyaneh (Tehran University of Medical Sciences, 2012)
Background:The effect of curcumin as a natural safe compound with different biological activities was examined on fungal growth and aflatoxin production in Aspergillus parasiticus NRRL 2999.Methods: The fungus was cultured in presence of serial two-fold concentrations of curcumin (125-2000 µg/ml) in yeast extract sucrose broth for 3 days at 28°C.Mycelia dry weight was determined as an index of fungal growth, while aflatoxin production was assessed by high performance liquid chromatography (HPLC). The expression of ver-1, nor-1, pksA, omtA and aflR genes in aflatoxin biosynthetic pathway was evaluated by real time PCR.Results: Curcumin strongly inhibited aflatoxin B1 production in the range of 26.6 to 94.9% by serial two-fold concentrations from 125 to 2000 µg/ml. Fungal growth was also inhibited by the compound in the range of 34.0 to 60.8%. Analysis of the expression of aflatoxin pathway genes by real time PCR showed that curcumin inhibited the expression of ver-1, nor-1, pksA,omtA and aflR genes at concentrations of 250 and 1000 µg/ml.In concentration of 1000 µg/ml, gene expression was reduced by 31.3%, 44.6%, 57.1% 110.9% and 286.7% accordingly. Reduction in the expression of aflatoxin biosynthesis genes was significant only for aflR. In ferric reducing ability of plasma (FRAP)assay,curcumin showed strong antioxidant activity at all concentrations tested.Conclusion: Curcumin may be employed successfully as a good candidate in controlling of toxigenic fungal growth on food and feed and subsequent contamination with aflatoxins in practice.